2022
DOI: 10.3390/healthcare10081408
|View full text |Cite
|
Sign up to set email alerts
|

The Link between Job Demands, Burnout, and the Self-Undermining of Healthcare Employees during the COVID-19 Pandemic: An Underestimated Threat?

Abstract: Previous studies have shown an association between job demands and burnout in medical staff during the pandemic. However, these studies have ignored the possibility of loss cycle occurrence during the crisis. In order to address this gap, the aim of this study was to test the mediating role of burnout in the positive relationship between job demands and the self-undermining of healthcare employees during the COVID-19 pandemic. Self-undermining represents the set of behaviors that generate obstacles and diminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 28 publications
0
1
0
4
Order By: Relevance
“…Based on a moderated mediation model, Shin et al (2020) found a positive correlation between role ambiguity and emotional exhaustion as well as a positive association between emotional exhaustion and turnover intention. Furthermore, Golu et al (2022) identified emotional exhaustion as a mediator between work–family conflict, which could be considered to be a form of role conflict that can undermine the self. For employees, including faculty members, who are considering leaving their organizations, especially if they do not have another job, this behavior could be considered to be a form of self-undermining.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a moderated mediation model, Shin et al (2020) found a positive correlation between role ambiguity and emotional exhaustion as well as a positive association between emotional exhaustion and turnover intention. Furthermore, Golu et al (2022) identified emotional exhaustion as a mediator between work–family conflict, which could be considered to be a form of role conflict that can undermine the self. For employees, including faculty members, who are considering leaving their organizations, especially if they do not have another job, this behavior could be considered to be a form of self-undermining.…”
Section: Discussionmentioning
confidence: 99%
“…Indonesia telah banyak melonggarkan pembatasan-pembatasan yang telah terjadi selama pandemi, termasuk banyak sekolah, perguruan tinggi, dan kantor-kantor di kota-kota besar telah beraktivitas seperti saat-saat normal. Penelitian sebelumnya yang membahas mengenai tuntutan kerja dan burnout, dibeberapa tahun terakhir lebih berfokus pada pekerja sebagai tenaga kesehatan karena pandemi COVID-19 yang mengharuskan tenaga kesehatan bekerja lebih dan menimbulkan tingkat tuntutan tinggi, sehingga pada akhirnya menyebabkan burnout pada karyawan (Bakker et al, 2014;Golu et al, 2022). Berdasarkan hal tersebut, peneliti tertarik untuk meneliti terkait dengan hubungan tuntutan kerja dan burnout dengan motivasi kerja sebagai moderator bagi karyawan generasi Z yang belum diteliti pada beberapa penelitian referensi sebelumnya.…”
Section: Hubungan Antara Tuntutan Kerja Dan Burnout Dengan Motivasi K...unclassified
“…Penelitian sebelumnya dari Bakker et al (2014) meneliti hubungan tuntutan kerja terhadap burnout pada karyawan usia beragam, yaitu dari usia 20 hingga 50 tahun. Penelitian Golu et al (2022) menemukan hubungan yang signifikan antara tuntutan kerja dan burnout yang diteliti pada karyawan secara umum, yaitu berusia 20 hingga 50 tahun. Penelitian yang telah ada dilakukan dengan sampel para karyawan diberbagai usia.…”
unclassified
See 2 more Smart Citations